1977
DOI: 10.1007/bf02498526
|View full text |Cite
|
Sign up to set email alerts
|

Some structural characteristics of iron oxyhydrate obtained electrochemically

Abstract: Being technological processes, sorptton and copreclpitation are Important in chemical manufacturing plants. They also have an important bearing on the purification of natural water and mine water involving removal of organic and inorganic impurities by aluminum and iron oxyhydrates (hydroxides).At the Mining Institute, Siberian Branch, Academy of Sciences of the USSR comparative investigations have been performed on removal of finely dispersed organic and inorganic impurities by reagent coagulation and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…One possible explanation for the truncation is that, at large radii, the thin HI disks become fully ionized by the metagalactic UV background (Bochkarev & Sunyaev 1977). If this is the case, the outer parts of gaseous disks should be emitting Hα photons.…”
mentioning
confidence: 99%
“…One possible explanation for the truncation is that, at large radii, the thin HI disks become fully ionized by the metagalactic UV background (Bochkarev & Sunyaev 1977). If this is the case, the outer parts of gaseous disks should be emitting Hα photons.…”
mentioning
confidence: 99%
“…This sharp drop is largely due to photoionization of the neutral hydrogen by the extragalactic radiation field and represents one way of defining the edge of an Hi disk. This was first explained by Bochkarev & Siuniaev (1977) and later by Maloney (1993) who suggested that the ionization fraction sharply increases at a critical column density of a few times 10 19 cm −2 , irrespective of galaxy mass or halo parameters. An example of this sharp drop-off in Hi is the KAT-7 observations of M83, which revealed a steep decrease in N HI at the edge of the galaxy disk (Heald et al 2016).…”
Section: Fraction Of Low N Himentioning
confidence: 87%
“…Since many of these invariably rely on some set of model assumptions, they provide only upper or lower limits rather than specific measurements. For example, observations of a sharp cutoff in the surface density of H I in the outer disks of nearby galaxies can constrain J ν LL (Bochkarev & Sunyaev 1977). Typical estimates lie in the range J ν LL ∼ 1 − 10 × 10 −23 erg s −1 cm −2 sr −1 Hz −1 , with the range of values dictated mainly by the assumed structure of the galactic disks (Corbelli & Salpeter 1993;Maloney 1993;Dove & Shull 1994).…”
Section: Comparison Of Local Estimates Of J ν Llmentioning
confidence: 99%